Influence of Accountability and Transparency on the Quality of Financial Reports At The BKAD Sumedang - Kartiwa, Aa; Rostianna, Sherlina; Farman, Fanji (LPPM Universitas Sebelas April, 2025)
This study aims to determine the effect of Accountability and Transparency on the Quality of Regional Financial Reports. The object of this study is the Regional Finance and Asset Agency of Sumedang Regency. This study is quantitative and uses primary data. The data collection method uses the Non Probability Sampling technique with the Purposive Sampling method, by distributing questionnaires to 42 respondents as samples. The analysis technique used is multiple linear regression analysis, hypothesis testing, correlation coefficient testing and determination coefficient using IBM SPSS version 25. Based on the results of partial hypothesis testing with the t test for the accountability variable from the significance value of 0.002<0,05 with a ttest coefficient of 3.404> ttable 2.02269 and the transparency variable shows a significance value of 0.000<0,05 with a ttest coefficient of 5.779> ttable 2.02269 which means that accountability and transparency of financial reports have a positive and significant effect on the quality of regional financial reports. Meanwhile, simultaneously with the f test, it shows that the significance value is 0.001<0,05 with a calculated f coefficient of 95.778>f table 3,2380 , which means that the accountability and transparency of financial reports have a positive and significant effect simultaneously on the quality of regional financial reports.